Analysis of the Effect of Motivation on Work Discipline During the Covid-19 Period in Indonesia - Nurhayana, Nurhayana (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The research was conducted at PT. Pioneer of the Protection of National Electrical Installations in Riau and Riau Islands Region. The purpose of this study was to determine the effect of motivation on the work discipline of employees of PT. Pioneer of the Protection of National Electrical Installations in Riau and Riau Islands Region. Data analysis in this study used quantitative methods. The samples taken in this study amounted to 32 people, the result of t-count 2.746 is greater than t-table 2.042. So it can be concluded that there is a significant effect of compensation on employee work discipline, the R Square result is 0.201, this explains that compensation has an effect on work discipline of 20.1%. And the remaining 79.9% is influenced by other independent variables not examined in this study. Keywords: Motivation and Work Discipline